Phenylalanine ammonia-lyase gene families in cucurbit species: Structure, evolution, and expression - Chun-juan DONG; Ning CAO; Zhi-gang ZHANG; Qing-mao SHANG (Journal of Integrative Agriculture, 2016)
Phenylalanine ammonia-lyase (PAL), the first enzyme of phenylpropanoid pathway, is always encoded by multigene families in plants. In this study, using genome-wide searches, 13 PAL genes in cucumber (CsPAL1–13) and 13 PALs in melon (Cm-PAL1–13) were identified. In the corresponding genomes, ten of these PAL genes were located in tandem in two clusters, while the others were widely dispersed in different chromosomes as a single copy. The protein sequences of CsPALs and CmPALs shared an overall high identity to each other. In our previous report, 12 PAL genes were identified in watermelon (ClPAL1–12). Thereby, a total of 38 cucurbit PAL members were included. Here, a comprehensive comparison of PAL gene families was performed among three cucurbit plants. The phylogenetic and syntenic analyses placed the cucurbit PALs as 11 CsPAL-CmPAL-ClPAL triples, of which ten triples were clustered into the dicot group, and the remaining one, CsPAL1-CmPAL8-ClPAL2, was grouped with gymnosperm PALs and might serve as an ancestor of cucurbit PALs. By comparing the syntenic relationships and gene structure of these PAL genes, the expansion of cucurbit PAL families might arise from a series of segmental and tandem duplications and intron insertion events. Furthermore, the expression profiling in different tissues suggested that different cucurbit PALs displayed divergent but overlapping expression profiles, and the CsPAL-CmPAL-ClPAL orthologs showed correlative expression patterns among three cucurbit plants. Taken together, this study provided an extensive description on the evolution and expression of cucurbit PAL gene families and might facilitate the further studies for elucidating the functions of PALs in cucurbit plants.